POSTGLACIAL PALAEOCEANOGRAPHY IN THE SKAGERRAK - Gyllencreutz R.; Backman Ja.; Jakobsson M.; Kissel C.; Arnold E. (My University, 2006)
Crucial periods of change in the latest glacial to early-Holocene palaeogeographic and palaeoceanographic evolution in the Skagerrak region are portrayed in four time-slice maps on a calibrated age scale at 14.0 kyr, 11.2 kyr, 10.2 kyr and 8.1 kyr. The course of palaeoenvironmental events is set in a high-resolution chronological framework using IMAGES core MD99-2286 and a grid of chirp sonar profiles. These maps visualize the complex, rapid palaeogeographic and palaeoceanographic changes during the glacial-interglacial transition, which is characterized by major changes in circulation, sediment sources, and depositional processes.
Keywords: PALAEOCEANOGRAPHY; PALAEOGEOGRAPHY; MARINE COASTAL PALAEOENVIRONMENTS; HOLOCENE; SKAGERRAK; HOLSMEER PROJECT; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен